2008
DOI: 10.4314/ajtcam.v4i4.31242
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical And Antimicrobial Effects Of <i>Chrozophora senegalensis</i>

Abstract: The in vitro antimicrobial activities of the whole plant extract (ethanolic-CEE) of Chrozophora senegalensis and its fractions (ethyl acetate-EAA, n-butanol-NBE, aqueous-AQE) were assayed using the agar plate diffusion and nutrient broth dilution methods. Test microorganisms were Bacillus subtilis (NCTC 8326 B76), Escherichia coli (ATCC 11775), Pseudomonas aeruginosa (ATCC 10145), Staphylococcus aureus (ATCC 021001). Aspergillus flavus, Aspergillus niger, Candida albicans and Salmonella typhi -laboratory isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 9 publications
(8 reference statements)
0
17
0
Order By: Relevance
“…Whereas no literature data were available for Chrozophora oblongifolia, other plants of the genus Chrozophora were phytochemically and biologically evaluated. So a strong antimicrobial activity of C. verbascifolia, and C. senegalensis has been reported Usman et al, 2007). Moreover, the study on Chrozophora brocchiana revealed an antioxidant effect and the isolated brocchlin carboxylic acid and its methyl ester were responsible for the observed effect (Hawas, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas no literature data were available for Chrozophora oblongifolia, other plants of the genus Chrozophora were phytochemically and biologically evaluated. So a strong antimicrobial activity of C. verbascifolia, and C. senegalensis has been reported Usman et al, 2007). Moreover, the study on Chrozophora brocchiana revealed an antioxidant effect and the isolated brocchlin carboxylic acid and its methyl ester were responsible for the observed effect (Hawas, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…is a genus of the family Euphorbiaceae, and comprises about nine species distributed in the Mediterranean regions, tropical Africa and West Asia (Boulos 2000;The Plant List 2013). Chrozophora taxa were reported for different biological activities; antioxidant (Delazar et al 2006;Hawas 2007), antimicrobial (Vassallo et al 2006;Usman et al 2007) and anticancer (Jamil et al 2012). Furthermore, some Chrozophora species are used in traditional medicine for the treatment of diverse ailments (Dipankar et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, some Chrozophora species are used in traditional medicine for the treatment of diverse ailments (Dipankar et al 2011). Many phytochemical constituents have been reported from few species of the genus Chrozophora, including alkaloids, coumarins (Abdel-Sattar 1985), diterpenoids (Mohamed et al 1994(Mohamed et al , 1995Tabussum et al 2013), phenylpropanoid glycosides (Mohamed 2001), phenolic acids, tannins, anthraquinones, (Agrawal & Singh 1988;Usman et al 2007). Flavonoids were commonly reported in all species of the genus Chrozophora (Vassallo et al 2006;Hawas 2007;Tabussum et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is boiled with cereal foods and the pregnant women used a decoction of it as a body wash, also used as a remedy for syphilis; and treatment of intestinal pain, typhoid and boils (Usman et al, 2007;Benoit-Vical et al, 2008). The fruit juice is used as eye drops to treat more severe cases, a maceration of leaves and roots is drunk to treat loss of hair and diabetes, and a water extract of aerial parts caused an in-vivo hypoglycemic response in rats (Delazar et al, 2005).…”
Section: Scientific Classificationmentioning
confidence: 99%